First report of Streptococcus agalactiae isolated from Oreochromis niloticus in Piura, Peru: Molecular identification and histopathological lesions - Ortega Asencios, Yessica; Barreiro Sanchez, Frank; Bueno Mendizabal, Hamilton; Huancare Pusari, Karina; Ostos Alfonso, Henry; Manchego Sayan, Alberto; Pereira Figueiredo, Mayra Araguaia; Gomez Manrique, Wilson; Andrade Belo, Marco Antonio de [UNESP]; Sandoval Chaupe, Nieves (Elsevier B.V., 2016)
The aim of this study was to identify the bacterium Streptococcus agalactiae isolated in farmed Nile tilapia (Oreochromis niloticus) from Piura, Peru and to characterize the histopathological lesions caused by this pathogen. Sixteen tilapias were sampled with clinic signs of the disease such as erratic swimming, exophthalmia and haemorrhages on the body and fins. Qualitative PCR in real time and histopathological analysis were performed. Nine fishes positives to S. agalactiae were found. The main histopathological findings were fibrinosuppurative epicarditis, periesplenitis, meninigitis and panophtaltmitis with predominance of mononuclear infiltration in all tissues. The correlation between qPCR and histopathological findings demonstrated nine fish (prevalence of 56.25%) with Cq lower than 30, associated to high degree of tissue injuries. This study reports the first isolation of S. agalactiae by PCR in real time in tilapia farmed in Peru and characterizes the major histopathological changes caused by this bacterium. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: Bacteria; Inflammation; Fish farming; Tilapid; PCR